2014
DOI: 10.1111/jpi.12154
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces cardiac remodeling and improves survival in rats with isoproterenol‐induced heart failure

Abstract: Melatonin was previously shown to reduce blood pressure and left ventricular (LV) remodeling in several models of experimental heart damage. This study investigated whether melatonin prevents LV remodeling and improves survival in isoproterenol-induced heart failure. In the first experiment, four groups of 3-month-old male Wistar rats (12 per group) were treated for 2 wk as follows: controls, rats treated with melatonin (10 mg/kg/day) (M), rats treated with isoproterenol (5 mg/kg/day intraperitoneally the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 64 publications
5
68
0
1
Order By: Relevance
“…The usefulness of melatonin treatment for cardiovascular diseases has been reported . Melatonin supplementation protected against pathological cardiac remodeling induced by transverse aortic constriction and isoproterenol, and melatonin prevented mitochondrial fission and improved cardiac function in mice with diabetes through the SIRT1‐PGC1α pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of melatonin treatment for cardiovascular diseases has been reported . Melatonin supplementation protected against pathological cardiac remodeling induced by transverse aortic constriction and isoproterenol, and melatonin prevented mitochondrial fission and improved cardiac function in mice with diabetes through the SIRT1‐PGC1α pathway .…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of melatonin treatment for cardiovascular diseases has been reported . Melatonin supplementation protected against pathological cardiac remodeling induced by transverse aortic constriction and isoproterenol, and melatonin prevented mitochondrial fission and improved cardiac function in mice with diabetes through the SIRT1‐PGC1α pathway . Administration of melatonin in AMI patients with ST elevation, who presented early after symptom onset, was associated with a significant reduction in the infarct size and remodeling after primary percutaneous coronary intervention .…”
Section: Discussionmentioning
confidence: 99%
“…1,2,33 This study identified that expression of USP4 was downregulated in human failing heart samples and in a murine model of cardiac hypertrophy induced by pressure overload. Adenovirus-mediated gainand loss-of-function approaches indicated that decreased expression of endogenous USP4 promoted myocyte hypertrophy induced by Ang II in vitro, whereas restoration of USP4 significantly attenuated the prohypertrophic effect of Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were divided into four groups (n ¼ 5) randomly: 1) normoxia þ saline (NOR þ SAL), 2) normoxia þ melatonin (NOR þ MEL), 3) CIH þ saline (CIH þ SAL), and 4) CIH þ melatonin (CIH þ MEL). The rats were treated with CIH or normoxia and received melatonin (SigmaeAldrich, USA; 10 mg/kg body weight) [24,25] or the same dose of saline by daily intraperitoneal (ip) injection. During CIH treatment, rats were housed in controlled oxygen-concentration chambers (OxyCycler A84; Biospherix, Redfield, NY, USA).…”
Section: Animal Model and Experimental Protocolmentioning
confidence: 99%